2022
DOI: 10.1155/2022/9271823
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Marketing Performance Evaluating in Financial Services Sector of Project Management

Abstract: In any economy, the financial sector is interpreted as the driving force in the process of achieving growth through the appropriate and optimal allocation of resources to productive economic sectors. Financial institutions are defined as customer service providers. The generalization of the obtained results to the whole statistical population is the last step in this research. The research is a survey that can provide data on attitudes, feelings, beliefs, past behaviors, recorded behaviors, and the recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Significant coefficients must have a value equal to or greater than 1.96, the significance index. If the value of these values surpasses 1.96, it shows that the link between the constructs is valid and, consequently, that the study hypotheses have been confirmed [44].…”
Section: Step 5: Fitting the Structural Model Coefficients Of Signifi...mentioning
confidence: 86%
“…Significant coefficients must have a value equal to or greater than 1.96, the significance index. If the value of these values surpasses 1.96, it shows that the link between the constructs is valid and, consequently, that the study hypotheses have been confirmed [44].…”
Section: Step 5: Fitting the Structural Model Coefficients Of Signifi...mentioning
confidence: 86%